2005
DOI: 10.1002/elps.200410308
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of electrophoretic mobilities of peptides in capillary zone electrophoresis by quantitative structure-mobility relationships using the offord model and artificial neural networks

Abstract: The aim of this work was to explore the usefulness of empirical models and multivariate analysis techniques in predicting electrophoretic mobilities of small peptides in capillary zone electrophoresis (CZE). The data set consists of electrophoretic mobilities, measured at pH 2.5, for 125 peptides ranging in size between 2 and 14 amino acids. Among the existing empirical models, the Offord model (i.e., mu identical with Q/M(2/3)) gave the best correlation for the data set. A quantitative structure-mobility rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
1
38
0
2
Order By: Relevance
“…M is the molecular mass, and a and α are two constants determined experimentally which can vary between classes of chemical compounds (DNA, peptides, organic acids) (Jalali -Heravi et al, 2005 ).…”
Section: Zone Electrophoresismentioning
confidence: 99%
“…M is the molecular mass, and a and α are two constants determined experimentally which can vary between classes of chemical compounds (DNA, peptides, organic acids) (Jalali -Heravi et al, 2005 ).…”
Section: Zone Electrophoresismentioning
confidence: 99%
“…However, a more detailed comparison of the theoretical and experimental data indicated that the correlation is only weak [7,8]. Combination of the Offord model with a corrected steric substituent constant and molar refractivity descriptors improved, however, the predictivity of the model, especially for peptides containing basic amino acids [9]. Similarly, CZE of five model proteins resulted in the conclusion that a primitive continuum model is appropriate for predicting mobilities of proteins [10].…”
Section: Modeling Electrophoretic Migration Of Proteinsmentioning
confidence: 99%
“…One is to extend the two-variable QSPR models with further parameters to increase the descriptive power of the models and enhance the operational range to all the different groups of peptides [6,7]. The other approach suggests the use of nonlinear modeling methods, such as artificial neural networks (ANNs) to develop more accurate and robust QSPR models [4,[8][9][10][11]. Actually, ANNs were effectively used to address the reported shortcomings of the semiempirical models.…”
Section: Introductionmentioning
confidence: 98%